Effect of cranberry and proanthocyanidin in the inhibition of wear and dentin demineralized organic matrix degradation - Boteon, Ana Paula (2016)
The literature recognizes that one of the most effective strategies in minimizing the dentin tissue loss by erosive agents is the maintenance of its organic matrix, because this acts as a diffusion barrier to acid. However, the collagen tends to be degraded and has been increasingly used to search for agents that inhibit this process. There is evidence that the Cranberry and proanthocyanidin can inhibit matrix metalloproteinases (MMPs) which degrade the dentin collagen, but these agents have not been adequately evaluated in dental erosion. The aim of this dissertation was to analyze the role of Cranberry extract and proanthocyanidin applied as a local gel for inhibiting the dentin demineralized organic matrix degradation and hence minimizing wear of dentin subjected to erosion. To this end, two studies were conducted (article 1 and 2). The first evaluated the effect of different concentrations (placebo, 0.05%, 1%, 5% e 10%) and application time (1 and 5 minutes) of proanthocyanidin gels on dentin erosion. After gels application, the dentin blocks were subjected to 3 erosive cycles per day, during 5 days. Profilometry was used to quantify the dentin loss. In this case, proanthocyanidin not have shown a dose and time-response effect, but the results of this study suggests its efficacy on decreasing the deleterious effects of erosion on the dentin, since different proanthocyanidin gels were able to promote lower dentin wear when compared with the placebo gels. The second study evaluated the effect of different gels (proanthocyanidin, chlorexidine, Cranberry, NaF e placebo) in inhibition wear and demineralized organic matrix (DOM) degradation. Before the treatment, samples were demineralized by immersion in citric acid (0,87 M, 36 h). Then, the studied gels were applied once on dentin for 1 minute. Next, the samples were immersed in artificial saliva containing collagenase obtained from Clostridium histolyticum for 5 days. The response variable was depth of dentin loss measured by profilometry. The results of this study showed that Cranberry was able to reduce the dentin wear and collagen degradation, but the proanthocyanidin obtained the best results, confirming its effectiveness in preventing dentin erosion.